Influence of water washing treatment on Ulva prolifera-derived biochar properties and sorption characteristics of ofloxacin - Chenghu Yang (Nature Portfolio, 2021)
Abstract The influences of water washing treatment on the properties of Ulva prolifera-derived biochar (U.P-biochar) and its sorption characteristics of ofloxacin (OFL) were investigated. The results showed that the water washing treatment significantly changed the physiochemical structures of U.P-biochars, and improved the sorption capacity of OFL. The sorption capacity of OFL by U.P-biochar was closely dependent on pyrolysis temperature (200–600 °C) and equilibrium solution pH (3–11). Different sorption mechanisms (e.g. cation exchange, electrostatic attraction, H-bond and cationic–π and π–π interactions) were dominant for specific U.P-biochars under various pH regions (acidic, neutral and alkaline). Moreover, the unwashed and washed U.P-biochars prepared at 200 °C (BC200 and BCW200) showed a higher sorption capacity of OFL at pH = 7. The two-compartment first-order model provided an appropriate description of the sorption kinetics of OFL by BC200 and BCW200 (R 2 > 0.98), which revealed that the contribution ratios between the fast and slow sorption compartments (f fast /f slow, 1.55 for BC200 and 1.25 for BCW200) reduced after water washing treatment of U.P-biochar. The values of n for the Freundlich model were less than 1, which demonstrated that the sorption of OFL by BC200 and BCW200 was favourable and nonlinear. Also, the sorption of OFL by BC200 and BCW200 increased with an increase in solution temperature and the sorption process was spontaneous and endothermic. This study provides valuable information for being a primary consideration in the production and application of U.P-biochar.